AKTIVITAS ANTIMIKROBA EKSTRAK ETANOL JAMUR LINGZHI (Ganoderma lucidum) DENGAN METODE SOXHLET TERHADAP ZONA HAMBAT Candida albicans - Handrianto, Prasetyo; Hatidja, Siti Annurijati (Universitas Nahdlatul Ulama Sidoarjo, 2018)
Infectious disease is the type of disease that most people suffer from in developing countries, including Indonesia. One of the causes of infectious diseases is Candida albicans. Lingzhi mushroom (Ganoderma Lucidum) is one of the plants in Indonesia which has potential as an antimicrobial. This study aims to determine the antimicrobial ability of lingzhi mushrooms (Ganoderma lucidum) ethanol extract against Candida albicans. The research method uses soxhlet methods. The results showed bacterial inhibition zones at concentrations of 20 μg/ml (8.3 mm) in the inactive category, 40 μg/ml (9.3 mm) with the inactive category, 60 μg/ml (10.5 mm) with the category less active, 80 μg / ml (11.4 mm) with the active category, and 100 μg/ml (12.6 mm) in the very active category. It can be concluded that the extract of Ganoderma Lucidum has an effect to Candida albicans bacteria. Based on observational data analyzed with the Oneway Anova test, it obtained a significant value of .000. This showed that there were differences in inhibition zones formed from various concentrations. Based on research antimicrobial activity of lingzhi mushroom ethanol extract (Ganoderma lucidum) used soxhlet method had an effect to inhibitory zone of Candida albicans.